O estado da arte sobre juventude(s) na pós-graduação brasileira stricto sensu: pesquisas na área das ciências da saúde (1987-2010) - Silva, Marina Jorge da (2014)
Adolescence and youth are sociocultural categories that recently have been reaching social and political relevance. Knowledge has been produced about these categories, which are characterized as plural social groups, and it is important to contribute to multidisciplinary readings. In this perspective, the present research aims at investigating and mapping the production of knowledge about youth in the health area of Stricto- Sensu Post-graduation, according to the classification of the Coordination for the Improvement of Higher Education Personnel (CAPES), searching to contribute to State of the Art studies on this theme. To perform this mapping, data available on the Theses Portal of CAPES were used, covering all the material provided between 1987 and 2010. This is a descriptive research, consisting of documentary analysis, methodologically organized in 4 stages: 1. Survey of theses and dissertations, 2. Data organization, 3. Survey of Analysis Categories and 4. Analysis. In the first stage, the descriptors young, youth, adolescent, adolescence, generation, (inter)generational, majority and minority were used and 33.654 works have been found. In the selection of those which belonged to the Health Area, responded to the inclusion and exclusion criteria and which were not duplicated, 2.953 works were accepted, totalizing 8,77% of the initial number. These works have been classified in thematic bases, with the objective of recognizing their focus, and subsequently the abstracts considered relevant to the research were reread so they could be analytically systematized. The conducted analysis allows the assertion of a Post-graduation in Health panorama that is still incipient and dispersed concerning youth, in which the use of the descriptors adolescent and adolescence prevails, in a ratio of 3,84 works which use this term for each study that brings the concepts of young and/or youth . An empirical reading of the category prevails in more than 90% of the studies. It was also possible to verify the dominance of studies produced in Masters programs (74,60%) of Public Institutions of Higher Education concentrated on the Southeast region of Brazil, which consists of more than 60% of the studies. In the Health area, the subareas, respectively, Nursery, Health Sciences, Public Health, Medicine (Pediatricts), Collective Health, Physical Education, Health of Children and Adolescents and Nutrition concentrate dissertations and theses. The researched production is widely spread through 484 different Post-graduation programs and 1.514 different advisors. Although this production is diversified concerning production places, studies are concentrated on epidemiological, clinical and laboratorial aspects (53,3%), indicating a tendency in works produced in the Health Area: the focus on disease problems. It is believed that such diffusion might disfavor the strengthening of the debate about the theme, and it indicates the necessity of overcoming readings that put youth in more individual aspects.